INOVASI PROGRAM BANK SAMPAH MELALUI PEMBERDAYAAN MASYARAKAT SEBAGAI PROSES KOMUNIKASI PERUBAHAN SOSIAL - Hilman Ramayadi; Nopita Sariningsih (SOURCE : Jurnal Ilmu Komunikasi, 2020)
Waste management is essentially needed by the community in Lebak Regency to reduce waste buildup. The concept of trash bank as a solution in order to change the paradigm of society in waste management is a new innovation for peoples in kabupaten lebak. Therefore in this research, the researcher want to explain and study the communication process carried out by the management of the Barangbang Garbage Bank and how to adopt the innovation of the garbage bank program by the community in East Muara Ciujung Village, Lebak Regency. This study uses descriptive qualitative research methods. The results showed that the communication process carried out by the management of the Sampang Barangbang Bank was more about installing communication channels using print media, spatial planning and face-to-face communication. The results of the research show that the communication process carried out by the Barangbang Garbage Bank management more emphasis on the communication channel stage through the use of print media, spatial planning and face-to-face communication.Keywords:  Adoption of Innovation, Waste Bank Programs, Community Empowerment, Communication Process